(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The objective was to assess the chemical composition, cholesterol, fatty acid (FAs), and amino acid (AAs) profiles of buffalo cheese, butter, and ghee. Materials and Methods: Buffalo milk (raw) was collected from the Bangladesh Agricultural University (BAU) Dairy Farm, BAU, Mymensingh-2202, Bangladesh. Cheese, butter, and ghee were prepared at the Dairy Chemistry and Technology Laboratory, Department of Dairy Science, BAU, Mymensingh, Bangladesh, and subjected to subsequent analyses. The gross nutritional composition and AAs profile of milk were analyzed prior to the manufacture of cheese, butter, and ghee. The gross nutritional composition of milk and dairy products was analyzed by applying an automated milk analyzer and the Association of Agricultural Chemists techniques, respectively. The cholesterol, FAs, and AAs contents of cheese, butter, and ghee were determined by the Bangladesh Council for Scientific and Industrial Research, Dhaka, Bangladesh. Furthermore, atherogenic and thrombogenic indices were also calculated using reference equations. Results: The results indicated that the buffalo milk is a good source of first-rate nutrients (dry matter: 16.50%, fat: 7.50%, protein: 3.75%). Findings indicated that the butter was significantly rich with (p < 0.05) total solids and fat where higher (p > 0.05) protein, carbohydrate, and minerals were found in cheese. The saponification, Reichert-Meissl, Polenski, and Kirschner values of buffalo ghee were found to be 225, 30, 1.2, and 25, respectively. A significant (p < 0.05) variation was found in the cholesterol content of buffalo cheese, butter, and ghee. Butter and ghee had 40.14 and 39.57 mg more cholesterol, respectively, than cheese. The results revealed identical FA profiles except for C24:0 among the three dairy products where the major FA compositions were C4:0, C14:0, C16:0, and C18:0 and C18:1 cis-9. The atherogenicity index and thrombogenicity index of cheese, butter, and ghee were statistically similar (p > 0.05). Butter was found with the most conducive anti-atherogenic and anti-thrombogenic characteristics due to lower saturated and higher polyunsaturated FAs. However, all the AAs concentrations were statistically higher (p < 0.05) in cheese than in butter and ghee. Conclusion: To conclude, buffalo cheese is superior to butter and ghee as regards nutrient density, but consumers can choose other foods based on their choice. J. Adv. Vet. Anim. Res., 9(1): 144–154, March 2022 http://doi.org/10.5455/javar.2022.i579